2002
DOI: 10.1128/aem.68.6.3102-3107.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Enumeration of Naegleria fowleri in Surface Waters by Solid-Phase Cytometry

Abstract: A new method for the rapid and accurate detection of pathogenic Naegleria fowleri amoebae in surface environmental water was developed. The method is based on an immunofluorescent assay combined with detection by solid-phase cytometry. In this study we developed and compared two protocols using different reporter systems conjugated to antibodies. The monoclonal antibody Ac5D12 was conjugated with biotin and horseradish peroxidase, and the presence of cells was revealed with streptavidin conjugated to both Rphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…Briefly, light is provided by an air-cooled argon laser emitting at 488 nm, and the fluorescence emission is collected in the Aeromonas hydrophila The device is able to differentiate between labeled organisms and fluorescent particles present in the sample based on the optical and electronic characteristics of the signals generated (18). When this discrimination procedure is not used, all fluorescent events detected, including the background signal, are counted by the cytometer and can be manually distinguished by using an epifluorescence microscope (Olympus BX41) fitted on a motorized stage driven by the computer of the cytometer, as described elsewhere (5,18,20). Data obtained from manual microscope validation of bacteria were used to optimize the setting of the instrument and the automatic discrimination procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, light is provided by an air-cooled argon laser emitting at 488 nm, and the fluorescence emission is collected in the Aeromonas hydrophila The device is able to differentiate between labeled organisms and fluorescent particles present in the sample based on the optical and electronic characteristics of the signals generated (18). When this discrimination procedure is not used, all fluorescent events detected, including the background signal, are counted by the cytometer and can be manually distinguished by using an epifluorescence microscope (Olympus BX41) fitted on a motorized stage driven by the computer of the cytometer, as described elsewhere (5,18,20). Data obtained from manual microscope validation of bacteria were used to optimize the setting of the instrument and the automatic discrimination procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The recent development of solid-phase cytometry (ChemScanRDI; Chemunex, Ivry-sur-Seine, France) has been seen as a great stride forward in the field of quality control, since it represents a rapid and sensitive device for the enumeration of low concentrations of fluorescence-labeled cells in water samples (15). This system can be applied to the detection of pathogenic microorganisms when combined with specific labeling using FISH or IF (2,20,21).…”
mentioning
confidence: 99%
“…Patient's survival depends on an initial awareness of the organism and laboratory confirmation by growing it in a liquid axenic media or 1.5% non-nutrient agar plates, flagellation test, exposition to higher temperature, biochemical and molecular methods. 11,12 In the present case, the clinical and epidemiologic history demonstrated that the patient contracted PAM seven days after swimming in pond water during the unusually hot summer. Laboratory investigations confirmed the clinical suspicion.…”
Section: Discussionmentioning
confidence: 97%
“…However, the real incidence of this infection in this country is unknown due to a lack of experience in its diagnosis 13 and only clinical cases caused by N. fowleri and B. mandrillaris 3 10 15 have been described.…”
Section: Discussionmentioning
confidence: 99%